From industry to artworks by Lourdes Castro and Ângelo de Sousa: conservation studies on cast acrylic sheet - Babo, Sara Sobral (2021)
Acrylic sheet, a plastic based on poly(methyl methacrylate) (PMMA), became popular within artists during the 1960s, when it was also used by two major Portuguese artists, Lourdes Castro (*1930) and Ângelo de Sousa (1938–2011). Taking as a starting point their work with this material, this thesis seeks to expand knowledge about the use of PMMA in art, its stability, and preservation. Therefore, a survey on artworks containing PMMA in Portuguese collections, as well as research on the history of production of this material in Portugal, was conducted in parallel with a material study of acrylic sheets used by those artists, and sheets produced by two Portuguese companies from which production processes were investigated and compared. This study included an artificial ageing experiment conducted in a solarbox (λ > 300 nm) for 8000 h, besides the characterization of the samples combining optical microscopy, colorimetry, gravimetry, micro-indentation, Raman, infrared and ultraviolet-visible spectroscopies, size exclusion chromatography, thermogravimetry, and thermo-desorption-gas chromatography/mass spectrometry. For the survey, 137 artworks from 8 Portuguese art collections were considered, providing an overview of the use of this material by artists and of its condition. Artworks surveyed included paintings, sculptures, objects/reliefs, photography, installations and artist books. From the 69 authors, 48 were Portuguese and have used PMMA from the 1960s to nowadays. Most of the artworks were in good or fair condition, and the main problems observed were dust and dirt deposits, abrasion, and scratches. This research showed that PMMA sheet was produced in Portugal between 1955 and 2009. At least four companies operated during the 1960s and all except one, produced nacreous PMMA sheets from recovered monomer obtained by depolymerization of acrylic residues. The material used by Ângelo de Sousa falls within this category. Concerns about the quality of these sheets led to a comparative study between PMMA samples of different typologies and origins. Results revealed a connection between particular aspects of the production technique (polymerization conditions, organic additives, and origin of monomer) with the properties (molecular weight, hardness, thermal stability) and long-term behaviour of acrylic sheets. The pigment responsible for the nacreous effect in Ângelo de Sousa‘s acrylic sheets showed signs of instability during the photodegradation experience, and was identified as plumbonacrite, Pb5(CO3)3O(OH)2, by Raman microspectroscopy. Cleaning and polishing treatments (as the ones used by Lourdes Castro for finishing her artworks) were also investigated in terms of immediate and long-term effects in the samples that had presented higher and lower photostability in the artificial ageing experiment. Treatments‘ impact seems to be dependent of the particularities of the acrylic sheet under testing. This research highlights that not all acrylic sheets present the same stability, which may be relevant for establishing new monitoring plans and preventive conservation measures, as well as to consider when testing interventive treatments in this material.